2013
DOI: 10.1167/13.10.12
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting visual integration of form, motion, and color as revealed by visual masking

Abstract: When two similar visual stimuli are presented in rapid succession at the same location, they fuse. For example, a red and a green disk are perceived as one single yellow disk. Likewise, verniers with opposite offset directions are perceived as one vernier with an almost aligned vernier offset. In fusion, observers have no conscious access to the individual stimuli. Using transcranial magnetic stimulation (TMS), it has been shown that feature fusion for verniers can be modulated for about 400 ms in that either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Scharnowski et al ( 2009 ) and Pilz et al ( 2013 ) have found that stimuli perceived as fused in time (i.e., co-temporal) may in fact be initially processed as temporally segregated. In these studies, the authors used stimuli presented in sequence over short time intervals that lead to a temporally fused percept.…”
Section: What Happens In a Momentmentioning
confidence: 99%
See 2 more Smart Citations
“…Scharnowski et al ( 2009 ) and Pilz et al ( 2013 ) have found that stimuli perceived as fused in time (i.e., co-temporal) may in fact be initially processed as temporally segregated. In these studies, the authors used stimuli presented in sequence over short time intervals that lead to a temporally fused percept.…”
Section: What Happens In a Momentmentioning
confidence: 99%
“…In these studies, the authors used stimuli presented in sequence over short time intervals that lead to a temporally fused percept. They applied either TMS (Scharnowski et al, 2009 ) or masking (Pilz et al, 2013 ) at different delays to disturb information processing, and examined which of the two successive stimuli dominated the perception. This procedure allowed them to establish that the processing of the two successive stimuli can be disturbed distinctly and in turn.…”
Section: What Happens In a Momentmentioning
confidence: 99%
See 1 more Smart Citation
“…We like to add that vernier fusion, as well as color and motion fusion, can be manipulated also by light masks, instead of TMS (Pilz et al, 2013). …”
Section: Review Of Evidencementioning
confidence: 99%
“…In the primary visual cortex, specialized pathways are used to process contour and surface information: neurons will respond selectively to orientation, code line-ends, and edges, or they will be activated by information related to color or texture. Whichever model is used to understand how information is bound together to identify forms and objects, time is required, because ambiguities regarding which information belongs to which object is often ambiguous (Grossberg & Pilly, 2008;Pugeault, Wörgötter, & Krüger, 2010) and because it is also possible to mentally group or re-group objects (Pilz et al, 2013;Van Assche, Gos, & Giersch, 2008). A series of mechanisms are, thus, required to identify an object.…”
Section: Introductionmentioning
confidence: 99%